Frekwensi Sudut Iridokorneal Terbuka dan Tertutup Mata Sehat dari Sampel Acak di Poliklinik Mata Rumah Sakit Umum Pusat Dr. Sardjito, Yogyakarta - Mu'tasimbillah Ghozi Mu'tasimbillah Ghozi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The classification of primary glaucoma is based on the depth of the iridocorneal angle. Supartoto et al. found in Dr. Sardjito Hospital Yogyakarta, that the cases of angle-closure glaucoma were thee times more than the open-angle glaucoma.Kolker & Hetherington stated that the open-angle glaucoma are 60 - 70% of the primary glau- coma in adults: The study on the iridocorneal angle in normal eye of random samples at the Eye Clinic, Dr Sardjito Hospital was done. The results support the statement of Kolker & Hetherington.Key Words: iridocorneal angle – primary glaucoma – open angle glaucoma – angle closure glaucoma – ophthalmology